Level of Students Writing Apprehension of the English Department at Muhammadiyah Sidrap University - Nurul Fadhilah Suardi; Baso Jabu; Geminastiti Sakkir (Journal of Excellence in English Language Education, 2023)
This study aimed to determine students' writing apprehension levels with a Descriptive Quantitative Design. The researchers used a questionnaire to ascertain the degree of students' writing apprehension. The study's target population was the Muhammadiyah Sidrap University's English Department. In addition, cluster sampling was employed by the researchers to choose the representative sample to represent the population. To conduct the analysis, the researchers chose one class as a sample. A total of 35 students from the third semester made up the sample. In this research, out of 35 students enrolled in the English Department's third semester, 0 (or 0%) were identified as having a high degree of writing apprehension, 28 (or 80%) as having an average level, and 7 (20%) as having a high level.